Phonological Error of English Vowel by Korean Speaker in Korean Drama - Annisa Nurhijatul Kania; Havid Ardi (Universitas Negeri Padang, 2022)
English is used by many non-native English speakers from all around the world. Because of that, the mother tongue influences when they speak foreign language or their second language. Thus, this research analysed the error of English vowels pronounced by Korean Speaker based on phonetic and phonology. This research used descriptive method which according to this research means collecting language symptoms in the form of words. The data were collected from a Korean Drama entitled Descendant of the Sun in several episodes in a form of words. To obtain data, this research used listening method which listened directly by the researcher and then validated by a native speaker. The finding shows that there are six monophthongs and three diphthongs of English vowel which are incorrectly pronounced by the Korean Speakers. Those errors are /ə/, /e/, /eɪ/, /æ/, /ɑ/, /ʊ/, /ɪ/, /iə/, and /oʊ/ which are substituted by /ɛ/, /o/, /ɪ/, /ɔ/, /ʌ/, /u/, /ɪə/, /ɪ/, /ɛʌ/, /ɑ/.